Genotypic profiles of hepatitis B in African immigrants and their clinical relevance. Issue 6 (9th December 2016) - Thurnheer, Maria Christine; Edwards, Rosalind; Schulz, Thomas Ray; Yuen, Lilly; Littlejohn, Margaret; Revill, Peter; Bannister, Elizabeth; Chu, Melissa; Tanyeri, Firuz; Wade, Amanda; Biggs, Beverley‐Ann; Sasadeusz, Joseph
Abstract : Hepatitis B virus (HBV) from 40 adult African immigrants in Australia was characterized to determine the prevalence of different HBV genotypes and subgenotypes. A mutational analysis was then performed to determine the presence of clinically significant mutations and correlate them to clinical outcomes. Initial sequencing analysis revealed 13 with genotype A (32.5%), 13 with genotype D (32.5%), and 14 with genotype E (35%). Serology showed that 37 were HBeAg negative. Phylogenetic analysis identified a high prevalence (25%) of HBV subgenotype A1 in our cohort, a subgenotype which has been associated with more aggressive clinical disease. BCP/PC sequencing was obtained for 38 patients. BCP and/or PC mutations were identified in 36/38 (95%). The median viral load of all patients was 2995 IU/mL and most of the pathology results were within the normal range. Only one patient had an increased APRI score of 1.1 suggestive of cirrhosis. We present novel information on the HBV genotypes amongst the African population in Australia along with clinical correlates. The high prevalence of A1 subgenotype in this population supports the current Australian recommendation to commence hepatocellular carcinoma screening in Africans with chronic HBV from 20 years old.